Primary care physician continuity, survival, and end‐of‐life care intensity. (6th September 2021) - Hung, Peiyin; Cramer, Laura D.; Pollack, Craig E.; Gross, Cary P.; Wang, Shi‐Yi
Abstract: Objective: To examine the associations of primary care physician (PCP) care continuity with cancer‐specific survival and end‐of‐life care intensity. Data Sources: Surveillance, epidemiology, and end results linked to Medicare claims data from 2001 to 2015. Study Design: Cox proportional hazards models with mixed effects and hierarchical generalized logistic models were used to examine the associations of PCP care continuity with cancer‐specific survival and end‐of‐life care intensity, respectively. PCP care continuity, defined as having visited the predominant PCP (who saw the patient most frequently before diagnosis) within 6 months of diagnosis. Data Extraction Methods: We identified Medicare patients diagnosed at age 66.5–94 years with stage‐III or IV poor‐prognosis cancer during 2001–2012 and followed them up until 2015. Patients who died within 6 months after diagnosis were excluded. Principal Findings: Primary study cohort consisted of 85, 467 patients (median survival 22 months), 71.7% of whom had PCP care continuity. Patients with PCP care continuity tended to be older, married, nonblack, non‐Hispanic, and to have fewer comorbid conditions ( p < 0.001 for all). Patients with PCP care continuity had lower cancer‐specific mortality (adjusted hazard ratio: 0.93; 95% confidence interval [CI]: 0.91 to 0.95; p = 0.001) than did those without PCP care continuity. Findings of the 2001–2003 cohorts (nearly all of whom died by 2015) show no associations of overall end‐of‐life care intensity measures with PCP care continuity (adjusted marginal effects: 0.005; 95% CI: −0.016 to 0.026; p = 0.264). Conclusions: Among Medicare beneficiaries with advanced poor‐prognosis cancer, PCP continuity was associated with modestly improved survival without raising overall aggressive end‐of‐life care.